Enzymological Basis for Herbicidal Action of Glyphosate - Rubin, Judith L. (1982)
The effects of 1 millimolar glyphosate (N-[phosphonomethyl]glycine) upon the activities of enzymes of aromatic amino acid biosynthesis, partially purified by ion-exchange chromatography from mung bean seedings (Vigna radiata [L.] Wilczek), were examined. Multiple isozyme species of shikimate dehydrogenase, chorismate mutase, and aromatic aminotransferase were separated, and these were all insensitive to inhibition by glyphosate. The activities of prephenate dehydrogenase and arogenate dehydrogenase were also not sensitive to inhibition. Two molecular species of 3-deoxy-d-arabino-heptulosonate 7-phosphate (DAHP) synthase were resolved, one stimulated several-fold by Mn(2+) (DAHP synthase-Mn), and the other absolutely dependent upon the presence of Co(2+) for activity (DAHP synthase-Co). Whereas DAHP synthase-Mn was invulnerable to glyphosate, greater than 95% inhibition of DAHP synthase-Co was found in the presence of glyphosate. Since Co(2+) is a V(max) activator with respect to both substrates, glyphosate cannot act simply by Co(2+) chelation because inhibition is competitive with respect to erythrose-4-phosphate. The accumulation of shikimate found in glyphosate-treated seedlings is consistent with in vivo inhibition of both 5-enolpyruvylshikimic acid 3-phosphate synthase and one of the two DAHP synthase isozymes. Aromatic amino acids, singly or in combination, only showed a trend towards reversal of growth inhibition in 7-day seedlings of mung bean. The possibilities are raised that glyphosate may act at multiple enzyme targets in a given organism or that different plants may vary in the identity of the prime enzyme target.